Morphological and molecular characterization of Travassosinema viatorum n. sp. (Nematoda: Oxyuridomorpha: Travassosinematidae) from the invasive millipede Chamberlinius hualienensis Wang, 1956 (Diplopoda: Polydesmida: Paradoxosomatidae) in Okinawa, Japan - Morffe, Jans; García, Nayla; Hasegawa, Koichi (Zootaxa, 2023)
Travassosinema viatorum n. sp. (Nematoda: Oxyuridomorpha: Travassosinematidae) is described from the invasive millipede Chamberlinius hualienensis Wang, 1956 (Diplopoda: Polydesmida: Paradoxosomatidae) in Okinawa, Japan. Females of T. viatorum n. sp. resemble T. claudiae Morffe & Hasegawa, 2017; T. thyropygi Hunt, 1996 and T. travassosi Rao, 1958 by lacking both lateral alae and a contraction posterior to the vulva. The body length of T. viatorum n. sp. is shorter than the aforementioned species. It differs from T. claudiae and T. thyropygi by its comparatively longer oesophagus, more posterior vulva, lack of cuticular ribs in the alae of the umbraculum and in the position of the nerve ring and excretory pore. Travassosinema viatorum n. sp. can be differentiated from T. travassosi by the extension of the cephalic umbraculum and the smaller eggs. The phylogeny of T. viatorum n. sp. is inferred by the D2–D3 domains of the 28S rDNA. The new species is located in a monophyletic clade with other sequences of Travassosinema from millipedes. The comparison of the phylogenies of Travassosinema and their hosts points to host switching rather than coevolution as a mechanism to explain the host-nematode relationships. This constitutes the second species of the genus Travassosinema described from the Japanese archipelago and the first oxyuridomorph nematodes found in C. hualienensis.